Analisis Faktor yang Mempengaruhi Kepatuhan Wajib Pajak Bayar Pajak Kendaraan Bermotor di Kabupaten Kediri - Susilawati Susilawati; Eko Prasetyo (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Regional taxes in Indonesia can be classified based on the level of regional government, namely regional taxes at the provincial level and regional taxes at the district/city level. One source of regional tax revenue comes from motor vehicle tax (MVT) payments. The aim of this research is to analyze the influence of taxpayer awareness, application of E-Samsat, tax knowledge and tax sanctions on taxpayer compliance in paying motor vehicle tax in Kediri Regency. This research is a type of quantitative research with an associative approach. The number of samples used in this research was 100 respondents with the sampling technique used was Random Sampling. Data collection was carried out using the questionnaire method. The analysis technique used in this research is multiple linear regression analysis using several methods including descriptive statistical analysis, validity test, reliability test, classical assumption test (normality test, multicollinearity test, heteroscedasticity test, autocorrelation test), multiple regression analysis, f test and t test. In this research, the results showed that taxpayer awareness, application of E-Samsat, tax knowledge and tax sanctions had a positive effect on taxpayer compliance in paying motor vehicle tax at SAMSAT Katang Kediri.